Value of spraying in fruit culture - Martin, Henry Alba (My University, 1898)
Introduction: The present power of man to combat fungus disease and insects injurious to fruits and fruit trees is great. All that is necessary is for the fruit grower to make himself acquainted with the authoritative facts, and be able to apply the principles that some men by scientific investigations; by long and tedious experiments, have given him. It has been truthfully said, that spraying is one of the most important factors in aiding the successful orchardists. To have been a successful fruit raiser, fifty or a hundred years ago, this might not have been essentially true, for then insect pests and fungous diseases were so numerous because fruit plantations were widely scattered. The increased number of orchards makes easier the rapid spread of insects from farm to farm. Mountains, oceans and rivers, natural barriers which once stopped their progress, fail to do so now.
Citation: Martin, Henry Alba. Value of spraying in fruit culture. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Man; Fungus Disease; Fruits; Theses; Manuscripts (documents)